Basal expression of the inducible transcription factors c-Jun, JunB, JunD, c-Fos, FosB, and Krox-24 in the adult rat brain - Herdegen, Thomas; Kovary, Karla; Buhl, Anja; Bravo, Rodrigo; Zimmermann, Manfred; Gass, Peter (The journal of comparative neurology, 1995)
Jun, Fos, and Krox proteins are inducible transcription factors contributing to the control of gene expression. The elucidation of their individual expression patterns in the nervous system provides new insights into the ability of neurons to react with changes of gene expression to external stimulation under physiological or pathological conditions. The expression of c-Jun, JunB, JunD, c-Fos, FosB, and Krox-24 was investigated in the brain of untreated male Sprague-Dawley and female BDIX rats by immunocytochemistry using specific antibodies. JunD immunoreactivity (IR) labeled the highest number of neurons, being present in almost all neurons of the brain. JunD was expressed at high levels in those areas that also exhibit c-Jun, JunB, c-Fos, and FosB-IR, such as locus coeruleus, periolivary nuclei (ncl.), pontine and central gray, lateral lemniscal ncl., inferior and superior colliculi, leaflet of geniculate ncl., midline nuclei of thalamus, dorsomedial and paraventricular ncl. of hypothalamus, ncl. supraopticus, dorsolateral part of caudate putamen and lateral septal ncl. In contrast to the high number of JunD-positive neurons, c-Jun, JunB, c-Fos, and FosB proteins were detected in rather low numbers of neurons in these brain areas; the rank of the number of immunopositive neurons was c-Fos > JunB > c-Jun > FosB. Particularly high levels of expression were observed for c-Jun in medullary motoneurons, medial geniculate ncl., arcuate ncl., and dentate gyrus, and for JunB in the CA-1 area of the hippocampus and islands of Calleja. The zinc finger protein Krox-24 was expressed in many neurons of these brain areas, with only discrete Jun- and Fos-IR; additionally, many intensely labeled nuclei were present in spinal ncl. of the trigeminal ventromedial ncl. of the hypothalamus and the CA-1 area of the hippocampus. In the cerebellum, nuclear labeling was detected only for c-Jun, JunD, and Krox-24 in granule cells, JunD-IR was also found in glial cells of gray matter and fiber tracts, whereas glial c-Jun-IR was observed only in fiber tracts. Apart from a weak JunD-IR, some areas did not express Jun, Fos, and Krox proteins such as cuneate and gracile ncl., venterobasal. complex of thalamus, globus pallidum, and Purkinje cells of the cerebellum. Our data indicate that inducible transcription factors of the fos, jun, and krox gene families show patterns of individual expression in untreated animals, thereby reflecting different mechanisms and/or thresholds for induction under physiological conditions. © 1995 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 10. Oktober 2004
Gesehen am 18.08.2025